Nanocomposite polymer gel electrolyte based on LiBOB–cellulose acetate for lithium–oxygen battery / Siti Zafirah Zainal Abidin - Zainal Abidin, Siti Zafirah (Institute of Graduate Studies, UiTM, 2016)
This thesis focuses on the preparation and characterization of liquid electrolytes (LEs), polymer gel electrolytes (PGEs) and nanocomposite polymer gel electrolytes (NCPGEs). In this work, lithium bis(oxalato) borate (LiBOB) salt was incorporated as the source of charge carriers. LEs were first prepared by dissolving LiBOB in the solvent, γ-butyrolactone using various molar concentrations of LiBOB. The optimum conductivity (0.8 M LiBOB) of the liquid electrolyte was then gelled with different concentrations of cellulose acetate (CA) to form PGEs. The ionic conductivity of all electrolyte samples were calculated using the bulk resistance value obtained from the complex impedance plot in the frequency range between 100 Hz to 1 MHz. The ionic conductivity pattern of PGEs slightly increases at low cellulose acetate concentration and starts declining with increasing cellulose acetate content. The conductivity reaches a maximum value of 7.05 mS cm-1 for the electrolyte containing 2.4 wt.% CA at room temperature. This phenomenon is best clarified by the Breathing Polymeric Chain model. Although PGE has a high conductivity, its physical properties and dimensional stability need to be improved for practical application. Therefore, the highest conductivity of PGE was dispersed with different weight ratios of nanosized silica to obtain NCPGEs…